Azafullerene C59N in Donor–Acceptor Dyads: Synthetic Approaches and Properties. Issue 4 (26th November 2015) - Rotas, Georgios; Tagmatarchis, Nikos
Abstract: Energy conversion schemes have attracted considerable attention in recent years. A large amount of research effort has focused on fullerenes, particularly C60 and its derivatives, as suitable electron acceptors, owing to their outstanding properties. In this context, C59 N‐based donor–acceptor systems have lately attracted attention, owing to their exceptional energy‐and electron‐transfer properties. As a result, chemical derivatization of C59 N plays an important role in the realization of the aforementioned systems. The current Minireview aims to familiarize researchers with the main aspects of azafullerene synthesis, chemistry, and photophysical properties, while it mainly focuses on the synthetic methodologies employed for as well as on energy conversion schemes of azafullerene‐based donor–acceptor systems. Abstract : Energy conversion schemes : Donor–acceptor systems based on the azafullerene C59 N are reviewed. While focusing on the synthetic strategies, the properties of systems employing this azafullerene as electron or energy acceptor are also presented, unfolding both the synthetic access as well as the unique electronic properties of these systems. Both in dyads in solution as well as in solar cell devices, C59 N is revealed as a promising acceptor for energy conversion schemes.